CLONING AND EXPRESSION OF LEVANSUCRASE (SacB) GENE FROM BACILLUS LICHENIFORMIS MJ8 IN ESCHERICHIA COLI AND ENZYMATIC SYNTHESIS OF LEVAN - M. M. Omar; J. M. Awda (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
In this study, a highly levansucrase-producing strain was isolated, identified as Bacillus lichniformans MJ8, and registered with the accession number OM672244.1 in the NCBI database. The SacB gene responsible for levansucrase production was transferred from this bacterium into Escherichia coli. It was found that the gene contains 1449 bp nucleotides, encoding 482 amino acids. The gene has been given the accession number ON811641.1 in the NCBI gene bank. The transformation was achieved by a cloning the SacB gene to plasmid pTG19-T, which was transferred to Escherichia coli DH5α. The Escherichia coli BL21 (DE3), with pet-28a (+) vector, was used to express the gene. One mM IPTG is induces the cloned gene to produce SacB protein. The levansucrase activity was 14.31 U/ml after transformation. The study also included the identification and characterization of levan produced by the bacteria using HPLC and FTIR techniques.